The Implications of Cannabis Policy Changes in Washington on Adolescent Perception of Risk, Norms, Attitudes, and Substance Use - Claire E Blevins; Eliza Marsh; Kelsey E Banes; Robert S Stephens; Denise D Walker; Roger A Roffman (SAGE Publishing, 2018)
There is increasing interest in the effect of legalization (particularly recreational legalization) of cannabis on prevalence of use and related problems. However, there is no consensus about the impact of policy change on cannabis use, particularly among adolescents. Legalization may increase adolescent use through mediating factors such as perceived risk and normative beliefs regarding the use of cannabis. Washington State enacted Initiative 502 on December 2012, which legalized and taxed recreational cannabis for adults aged ⩾21 years. This paper used data from a randomized, controlled intervention trial for cannabis-using adolescents that was recruiting participants in Seattle before and after the policy change to evaluate the following goals: assess differences in substance use, problems, and symptomatology pre- and post-policy change; evaluate several proposed risk factors that may be associated with such differences; and describe participants' understanding of the law and how this understanding may relate to rates of use. Analyses revealed no significant differences pre- to post-policy in rate of substance use. However, there were significant post-policy increases in problems and use disorder symptoms. Despite these differences, there were no significant increases in norms, attitudes, or perceptions of risk. Participants were able to answer most questions regarding policy changes correctly, indicating a good understanding of the policy. Results provided no evidence that policy change influenced heavy-using adolescents' rates of use nor the proposed risk factors associated with problematic use patterns.